Дано, дуно ...Нимъёс уно: Имена знакомы - всеми любимы / Николай Емельянов - Емельянов Николай Николаевич (Буква, 2012)
Экземпляры: (20131105) / Инвентарный номер: 47550 / Цена: 100.00 / Сис.шифр: С(Удм) / Авт.знак: Е 60 / ББК: 84(2=Удм)6-5